Полет орлицы: [роман] / Дмитрий Агалаков - Агалаков Дмитрий Валентинович (Серия "Исторические приключения", 2007)
Экземпляры: ООВ (20140212) / Инвентарный номер: 35418 / Цена: [86.00] / Сис.шифр: 84(2Рос) / Авт.знак: А 23 / ГРНТИ: 17 / ББК: 84(2Рос)